THE STUDY OF OSCILLATIONS IN THE QUASI-REGULATED THREE-SPAN BEAMS - Zhelezniak, H. S.; Soldatov, K. I. (Science and Transport Progress, 2005)
The article, using the example of a three-flight irregular beam, studies the influence of irregularities of linear, stiffness- and mass-related parameters on the change of own frequencies. It has been shown that at certain parameters of irregularity it is possible to use in practical calculations simple solutions for regular schemes, the obtained approximated dependences, charts and nomograms.